2008
DOI: 10.1016/j.ijrobp.2008.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Outcome in Advanced Head-and-Neck Cancer Based on Tumor Blood Volume Alterations During Therapy: A Prospective Study

Abstract: Purpose To assess whether alterations in tumor blood volume (BV) and flow (BF) during the early course of chemo-radiation therapy (RT) for head and neck cancer (HNC) predict treatment outcome. Methods Fourteen patients receiving concomitant chemo-RT for non-resectable, locally advanced HNC underwent dynamic-contrast enhanced (DCE) MRI scans pre-therapy and two weeks after initiation of chemo-RT. BV and BF were quantified from DCE MRI. Pre-RT BV and BF as well as their changes during RT were evaluated separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 12 publications
(9 reference statements)
7
83
2
Order By: Relevance
“…The ability of DCE-MRI to predict a patient's response to chemo-radiation treatment has been previously investigated in head and neck cancers [5,7,8] . In a study by Cao et al [7] that followed head and neck cancer patients for a median of 10 mo (range, 5-27 mo), the blood volume in the primary gross tumor volume was increased significantly in local control patients after 2 wk of chemo-radiation, compared with local failure patients (P < 0.03) [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of DCE-MRI to predict a patient's response to chemo-radiation treatment has been previously investigated in head and neck cancers [5,7,8] . In a study by Cao et al [7] that followed head and neck cancer patients for a median of 10 mo (range, 5-27 mo), the blood volume in the primary gross tumor volume was increased significantly in local control patients after 2 wk of chemo-radiation, compared with local failure patients (P < 0.03) [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DCE-MRI to predict a patient's response to chemo-radiation treatment has been previously investigated in head and neck cancers [5,7,8] . In a study by Cao et al [7] that followed head and neck cancer patients for a median of 10 mo (range, 5-27 mo), the blood volume in the primary gross tumor volume was increased significantly in local control patients after 2 wk of chemo-radiation, compared with local failure patients (P < 0.03) [7] . In a study of 33 patients with head and neck cancer treated with neoadjuvant chemo-radiation therapy, Kim et al [8] found that the average pretreatment K trans value of a group with complete response to treatment was significantly higher than that of a group with partial response (P = 0.001) at a 6 mo follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related study, Zima et al 7 reported that patients with higher pretreatment blood volume and blood flow measurements from the primary tumor demonstrated better response and reduction in tumor volume after induction chemotherapy. Cao et al 8 observed a significant increase in tumor blood volume during the early course of chemoradiation therapy in patients who exhibited local control but there was no change in blood volume in patients who demonstrated local failure from chemoradiation. These studies focused only on prediction of short-term local therapeutic response, and there is no evidence to support the prognostic value of DCE-MRI in predicting long-term survival in HNSCC, which may be different from the short-term response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HNSCC with elevated tumor blood flow/ blood volume respond more favorably to chemoradiation therapy than patients with low blood flow/volume. [5][6][7][8][9] DCE-MRI studies yield a parameter called K trans , which is a measure of the first-order bidirectional volume transfer constant of contrast agent exchange between the intravascular plasma and tumor interstitium compartments. The pretreatment K trans , which reflects tumor perfusion/permeability, has been shown to predict nodal treatment response to chemoradiation therapy in patients with HNSCC.…”
mentioning
confidence: 99%